Consumer Behavior, Marketing, and Supply Chains of Fermented Foods and Health Supplements in Southeast Asia and India - Vaigarai Senthil; Bhagavathi Sundaram Sivamaruthi; Wandee Rungseevijitprapa; Chaiyavat Chaiyasut; Venkatachalam Sivakumar (Community and Social Development Journal, 2026)
Fermented foods and health supplements are deeply embedded in the dietary traditions of Southeast Asia and India and are increasingly positioned within expanding functional food and preventive health markets. This narrative review aimed to synthesize evidence on four interrelated domains: consumer behavior, marketing dynamics, supply-chain systems, and regulatory and certification issues associated with fermented foods and health supplements in these regions. Peer-reviewed literature was searched primarily through Scopus and Web of Science, with supplementary searches in ScienceDirect, SpringerLink, Emerald Insight, and Taylor & Francis Online, with no year restriction. Studies were screened for relevance to fermented foods and/or health supplements in Southeast Asia and India and were synthesized using thematic and interpretative analysis. The review found that health consciousness, perceived efficacy and safety, cultural familiarity, affordability, physician recommendations, and product credibility are major determinants of consumer acceptance and purchase intention. Digital marketing, e-commerce, social media engagement, influencer communication, and branding increasingly shape market access and consumer trust, particularly among younger and urban populations. Supply-chain development is constrained by limited cold-chain infrastructure, inconsistent standardization, dispersed sourcing, and variable quality control, whereas transparency, traceability, digital logistics, and omnichannel coordination can enhance efficiency and market responsiveness. Regulatory inconsistencies and differences in certification and labeling requirements remain important barriers to consumer confidence and cross-border market expansion. Conceptually, the review proposes a reciprocal ecosystem model in which consumer trust functions as a cross-cutting mechanism linking perceived health value, marketing credibility, certification, product quality, and supply-chain transparency, while regulatory, cultural, and technological factors condition these relationships. Greater regulatory harmonization, scientific validation of health claims, improved supply-chain infrastructure, and comparative cross-country research are recommended to support sustainable market growth and strengthen benefits for consumers, local producers, and communities.